Phototherapy and photochemotherapy in dermatology. Recommendations of the Polish Dermatological Society - Placek, Waldemar; Kaszuba, Andrzej; Lesiak, Aleksandra; Maj, Joanna; Narbutt, Joanna; Osmola-Mańkowska, Agnieszka; Wolska, Hanna; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2019)
Light is a component of the electromagnetic waves. The electromagnetic wave consists of mutually inducible electrical and magnetic components that generate variable electric field. This then turns into magnetic field, causing alternating current to flow. Electromagnetic waves include radio waves, microwaves, infrared light, visible light, ultraviolet light, X-rays and gamma radiation. The length of these waves determines their properties. An increase in wavelength is accompanied by a decrease in its radiation energy. Dermatological phototherapy uses the following types of light: broadband UVB, narrow-band monochromatic UVB, laser UVB, UVA in combination with psoralens – PUVA, UVA1, visible light, monochromatic light within the visible spectrum: violet, yellow, red, deep red and infrared. Phototherapy and photochemotherapy nowadays uses equipment emitting radiation at the following lengths: UVB 311, UVB 313, UVB 308, UVA 320–400 nm with a peek at 365 nm and 340–400 nm UVA1. In Poland, the most commonly used radiation is UVB 311 and UVA 320–400 mm (mainly with psoralens). Photochemotherapy is a form of treatment by light, in which the effect of ultraviolet in combination with chemical substances acting as photosensitizers (psoralens) is utilized. The term PUVA was introduced in 1974 by Parrish et al. in a publication assessing the results of psoriasis treatment with orally administered 8-methoxypsoralen and whole-body exposure to long-wave UVA radiation. This article contains the recommendations of the Polish Dermatological Society for photoherapy and photochemoterapy in dermatology.